Design of triple band microstrip patch antenna for multipurpose application - Nur Ali, Omar (2022)
A multipurpose triple-band microstrip patch antenna with frequencies of 2.45 GHz, 3.66 GHz, and 4.46 GHz has been constructed. The proposed antenna is fed by 50 ohm microstrip feed lines. Inserting five rectangular slots in the patch improves the impedance bandwidth, gain, and reflection coefficient. The antenna was constructed on FR 4 substrate of (Ɛr=4.3) with a loss tangent of 0.035. The overall dimensions of the antenna are 29 × 38 × 1.6 mm. The simulation results were generated using CST Microwave Studio. The reflection coefficient (S11) operates at –26.7 dB at 2.45 GHz, -24.1 dB at 3.66 GHz, and -54.9 dB at 4.46 GHz. The gain of the design is 4.08 dB, 3.49 dB and 3.49 dB at 2.45 GHz, 3.66 GHz and 4.46GHz, respectively, with a VSWR of less than 2.0. The proposed antenna covers a large section of the ISM-S and C bands. Because of its tiny size, narrow bandwidth, and appropriate gain can be incorporated in mobile devices for mobile WiMAX, Wi-Fi, Bluetooth, and WLAN operations. It can also be used for surveillance and communication by weather radar, surface ship radar, and some communications satellites. As a result, the presented microstrip rectangular patch antenna could be helpful for ISM, S, and C bands applications.